Expanding the search for emerging mental ill health to safeguard student potential and vocational success in high school: A narrative review. Issue 6 (5th February 2020) - Bowman, Siann; McKinstry, Carol; Howie, Linsey; McGorry, Patrick
Abstract: Aim: Young people experiencing mental ill health are more likely than their healthy aged peers to drop out of high school. This can result in social exclusion and vocational derailment. Identifying young people at risk and taking action before an illness is established or school dropout occurs is an important goal. This study aimed to examine evidence for the risk markers and at risk mental states of the clinical staging model (stage 0‐1b) and whether these risk states and early symptoms impact school participation and academic attainment. Method: This narrative review assembles research from both the psychiatry and education literature. It examines stage 0 to stage 1b of the clinical staging model and links the risk states and early symptoms to evidence about the academic success of young people in high school. Results: In accordance with the clinical staging model and evidence from education literature, childhood trauma and parental mental illness can impact school engagement and academic progress. Sleep disturbance can result in academic failure. Undifferentiated depression and anxiety can increase the risk for school dropout. Subthreshold psychosis and hypomanic states are associated with functional impairment and high rates of Not in Employment, Education, or Training (NEET) but are not recognized in the education literature. Conclusion: Risk markers for emerging mental ill health can be identified in education research and demonstrate an impact on a student's success in high school. Clear referral protocols need to be embedded into school life to reduce risk of progression to later stages of illness and support school participation and success.